Nocardiosis: An Essential Diagnostic Challenge in Suspected Pulmonary Tuberculosis - Asem Ali Ashraf1; Pratibha Bhat U.1* (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Nocardiosis is a globally recognized opportunistic infection that predominantly affects immunocompromised individuals, leading to a diverse range of clinical manifestations, from cutaneous to severe systemic forms. The similarity of pulmonary nocardiosis symptoms to those of pulmonary tuberculosis often leads to misdiagnosis, presenting a significant diagnostic challenge for clinicians. We present an illustrative case of a 48- year-old male, newly diagnosed with HIV, who exhibited symptoms initially suggestive of pulmonary tuberculosis but was subsequently diagnosed with pulmonary nocardiosis. Methods: Bronchoalveolar lavage (BAL) fluid samples were obtained and subjected to microbiological culture, Gram staining, and modified acid-fast (Ziehl-Neelsen) staining for the identification of Nocardia species. Results: Gram staining of BAL fluid revealed thin, branched, beaded, filamentous, Gram-positive bacilli. Modified acid-fast staining identified branching acid-fast bacilli (1-2 organisms per high-power field (HPF)), consistent with Nocardia. Diagnosis of Nocardia is crucial as it necessitates targeted therapy, particularly in immunocompromised hosts. Nocardia was cultured after one week, highlighting its slow growth characteristic, which can delay diagnosis and treatment. The patient was commenced on trimethoprim-sulfamethoxazole (800/160 mg four times daily), showing significant clinical improvement within two weeks. After 12 months of treatment, there was complete resolution of symptoms, radiological improvement, and normalization of laboratory parameters, indicating successful treatment of pulmonary nocardiosis. Conclusion: Pulmonary nocardiosis must be considered in immunocompromised patients with persistent respiratory symptoms. Comprehensive imaging and bronchoscopy with BAL are pivotal for effective sample collection and accurate laboratory diagnosis. Modified Ziehl-Neelsen staining is critical for the definitive identification of Nocardia infection. Early and proactive screening in high-risk groups, such as HIV patients, cancer patients, or organ transplant recipients, is crucial for the prompt initiation of targeted therapy, typically with trimethoprimsulfamethoxazole, to improve outcomes.